2012
DOI: 10.1056/nejmoa1200690
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Activity, and Immune Correlates of Anti–PD-1 Antibody in Cancer

Abstract: Background Blockade of programmed death 1 (PD-1), an inhibitory receptor expressed by T cells, can overcome immune resistance. We assessed the antitumor activity and safety of BMS-936558, an antibody that specifically blocks PD-1. Methods We enrolled patients with advanced melanoma, non–small-cell lung cancer, castration-resistant prostate cancer, or renal-cell or colorectal cancer to receive anti–PD-1 antibody at a dose of 0.1 to 10.0 mg per kilogram of body weight every 2 weeks. Response was assessed after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

130
9,342
13
132

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11,010 publications
(9,617 citation statements)
references
References 26 publications
130
9,342
13
132
Order By: Relevance
“…Recent preclinical and clinical studies have demonstrated that checkpoint blockade using anti‐CTLA‐4, anti‐PD‐1, and anti‐PD‐L1 antibodies can be successful for cancer immunotherapy 17, 18, 19. Therefore, it is important to assess whether T‐cell regulatory molecules can be used as biomarkers to predict tumor resistance and guide the choice of therapy, which is why we investigated the preoperative serum levels of B7 family molecules and CD28 family receptors in RCC patients as well as their associations with clinicopatological features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent preclinical and clinical studies have demonstrated that checkpoint blockade using anti‐CTLA‐4, anti‐PD‐1, and anti‐PD‐L1 antibodies can be successful for cancer immunotherapy 17, 18, 19. Therefore, it is important to assess whether T‐cell regulatory molecules can be used as biomarkers to predict tumor resistance and guide the choice of therapy, which is why we investigated the preoperative serum levels of B7 family molecules and CD28 family receptors in RCC patients as well as their associations with clinicopatological features.…”
Section: Discussionmentioning
confidence: 99%
“…reported that PD‐L1 overexpression by tumors in vivo and in vitro leads to immune tolerance, whereas blockade of PD‐L1 or PD‐1 enhances antitumor immunity 24. Blockade of the PD‐L1/PD‐1 interaction achieves a durable response in approximately 30% of patients with ccRCC, and the response seems to be related to the tumor level of PD‐L1 expression 17, 18. However, it remains challenging to select patients who are likely to respond to anti‐PD‐1/PD‐L1 therapy 12.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the PD‐1/PD‐L1 axis is present and may be dysregulated in human sepsis 11, 48. In oncology, anti‐PD‐1 and anti‐PD‐L antibody therapy have been used successfully to treat various tumors 49. These data indicate that blocking the PD‐1/PD‐L1 axis is a promising target for restoring immune function in human sepsis.…”
Section: Immunological Modification Therapiesmentioning
confidence: 95%
“…Within the last decade, treatment of metastatic melanoma (MM) has been revolutionized by a wide array of immunotherapies including checkpoint inhibitors against CTLA-4 1 and PD-1/PD-L1 2 , 3 as well as adoptive cell therapy (ACT). 4-6 However, despite great advances, treatment responses are restricted to a fraction of patients.…”
Section: Introductionmentioning
confidence: 99%